Implementation of the Pentahelix Model in Community-Based Downstreaming of Non-Timber Forest Products (NTFPs) in Kerinci Regency (International Journal of Scientific Research and Management (IJSRM), 2023)
Accelerated downstreaming of Non-Timber Forest Products (NTFPs) products can be achieved if cooperation and coordination between relevant stakeholders (multi-stakeholders) goes well, so that sustainable adoption of innovation can occur. This research aims to analyze the effectiveness of multi-party communication in community-based downstreaming of non-timber forest products. The research was carried out in August-October 2023 in Kerinci Regency. This research used a qualitative method, with key informants being the Head of the Kerinci Production Forest Management Unit (KPHP), the Social Forestry Business Group (KUPS), Companions, Non-Governmental Organizations (NGOs), as well as community members of the HHBK processing business. Data collection was carried out through Focus Group Discussion (FGD), using questionnaires, interview guides and observations. Secondary data was obtained from KPHP, Forestry Service and Kerinci Agriculture Service. Data were analyzed using N-Vivo analysis. The research results show that multi-party communication between non-timber forest product managers has not been effective. The interaction patterns of parties in the forest management network are not evenly distributed. The forest farmer group assisted by KPHP Kerinci has attempted to downstream processed products such as robusta coffee, kawa leaf, honey, cinnamon bark, cinnamon tea, coffee leaf dent, various taro chips, serundeng and so on, but are still constrained by market access and capital. , as well as its institutions. This means that the success of social forestry is not enough to only rely on strengthening one aspect, but must go hand in hand and complement each other.